(untitled) (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: The Global pandemic COVID-19 affects mainly adult population with serious devastating effects in some of them, particularly those with chronic comorbidities. It is less common in children and rare in neonates. Objectives: The aim of study was to identify the COVID-19 in neonates so that we can give proper emphasis on neonatal COVID-19. Methods: This cross sectional study was conducted from April 2020 to August 2020 at Dhaka Shishu (Children) Hospital in Bangladesh. Neonates with suspected COVID- 19 were tested for SARS-CoV-2 virus by RT- PCR and positive cases were included in the study. Data were collected and statistical analysis was done by SPSS version 26. Results: Out of 1714 admitted neonates, 32 (2%) cases were COVID-19 positive. Male were 21(67%) and female were 11 (33%). Majority of the cases (28,88%) were at term. Twelve (38%) cases were from Dhaka and 20 (62%) cases came from outside Dhaka. Only 4(13%) cases were found positive for SARS-CoV-2 virus by RT- PCR within 3 days, among them 2 (6%) cases were within 24 hours of age. Nine cases (28%) were RT-PCR test positive within 4-7 days and 19 cases (59%) were RT-PCR positive within 8-28 days. Most of the cases belonged to neonatal medicine (24,75%) and 8(25%) cases were associated with surgical diseases. Sepsis was present in 17(53%) cases, perinatal asphyxia in 8(25%) and pneumonia in 6(19%) cases. Fourteen cases were discharged after improvement, 12 were referred to COVID-19 designated hospital, 2 cases were transferred to corona unit and 4 cases died. Conclusion: In this study a good number of neonates were affected with COVID-19. Perinatal asphyxia, sepsis and pneumonia were common association with COVID-19. So for proper management and prevention of transmission of this disease, it should be properly addressed in neonates. DS (Child) H J 2020; 36(2): 101-106